Effect of sonic bloom frequency on the growth of red amaranth (Alternanthera amoena Voss). Issue 1 (June 2020) - Susilo, B; Fitriani, Y F
Abstract: Red amaranth (Alternanthera amoena Voss) is able to be used not only as food plants but also as herbal plants. Due to a high nutrient content of red amaranth, the demand of this plant is continue to increase. Even though this plant has high demand, its productivity is relatively low. The Sonic-bloom was experimented to be applied on the red amaranth cultivation to improve the productivity. The purpose of this research is to determine the effect of various frequencies and duration of sonic-bloom exposure on the growth of the red amaranth plant (Alternanthera amoena Voss). The frequencies were set at two levels i.e. 3000-5000Hz and 7000-9000 Hz with the exposure duration were 15, 30, 45, 60 and 75 minutes respectively. The results showed that the frequency and duration of exposure have a significant influence on the cultivation parameters of red amaranth plants. Frequency treatment of 3000-5000 Hz and 7000-9000 Hz produced plants with 25.93 cm and 18.83 cm of height, 13 strands of leaves, 42 cm and 30.6 cm of plants length, 2841.01 μm 2 and 3688.51 μm 2 of stomata area, and 14.84 gr and 7.58 gr of wet plant weight respectively. These results were significantly different compared to the control (without sonic bloom treatment) that have 8.53 cm of height, 7-13 strands of leaves, 14.87 cm of plants length, 972.98 μm2 of stomata area, and 0.55 gr of wet weight. The best treatment in this study is the frequency of 3000-5000 Hz with exposure duration of 75 minutes, concluding that Sonic Bloom technology is able to improve the productivity of red amaranth plants.